Perceived Neighborhood Social Cohesion and Preventive Healthcare Use - Kim, Eric S.; Kawachi, Ichiro (American journal of preventive medicine, 2017)
Neighborhood social cohesion has been linked with better health and health behaviors, but its association with patterns of preventive healthcare use remains understudied. The hypothesis was that people with higher perceived neighborhood social cohesion would display increased use of preventive healthcare services. Participants (N=7,168) were drawn from the 2006 wave of the Health and Retirement Study—a prospective and nationally representative panel study of American adults aged >50 years—and tracked for one wave (2 years). Analyses were conducted in 2016. After adjusting for sociodemographic factors and baseline health, each SD increase in neighborhood social cohesion was associated with a higher likelihood that people would obtain influenza vaccinations (OR=1.09, 95% CI=1.04, 1.15) or cholesterol tests (OR=1.10, 95% CI=1.02, 1.19). Further, women were more likely to receive mammograms/x-rays (OR=1.10, 95% CI=1.01, 1.19) or Pap tests (OR=1.08, 95% CI=1.00, 1.17). However, men were not more likely to receive prostate exams (OR=1.06, 95% CI=0.96, 1.17). With additional research, findings from this study may inform the development of new strategies that increase the use of preventive healthcare services and enhance the quality of life among people moving through the ranks of this aging society.